Pengembangan Pendidikan Karakter Melalui Pendidikan Kemandirian di Pondok Pesantren Kyai Mojo Tembelang Jombang - Afim - Irwansyah; Chusnul - Chotimah; Khoirun Nisa' (JoEMS (Journal of Education and Management Studies), 2020)
As an effort to develop character education for students one of them can be done by providing independence education, and for this study was conducted at Pondok pesantren Kyai Mojo Tembelang Jombang, in order to examine how to develop character throught independence education at Pondok Pesantren Kyai Mojo Tembelang Jombang, and the program ist independence program, and the supporting or inhibiting factors experienced. This research is a type of field research with a qualitative approach. With this qualitatitve approach the researcher tries to describe the process of developing character education through independence education using logics and theories that are appropriate to the field. Kyai Mojo Islamic Boarding School makes independence education the most important and fundamental thing in carrying out daily activities. Then in the form of 3 independence programs that are expected to develop the character of the students, namely the independence program in the from of: independence of worship, independence of teaching and learning, and economic independence. Then if the three programs can run smoothly and in an orderly manner, the students will be formidable and unyielding in facing various problems or problems.